GOODBYE GLOBAL HEALTH? - Blume, Stuart (Bulletin of the Institute of Ethnography SASA, 2021)
Over the past 20 or 30 years vast sums of money have gone into ‘global health’. The money has funded vast initiatives largely focused on infectious disease control, as well as university centres and research projects. The numerous and varied definitions of global health share a normative element. Global health implies an egalitarian approach, treating everyone’s health needs equally, irrespective of citizenship, ethnicity or gender. If we look at what the concept does in practice, other than lubricate the flow of funds, the picture becomes more complex. This essay argues that despite its normative connotations, global health is closely associated with globalization. It became an arena for engaging in contests for economic and strategic advantage under cover of its normative connotations. This ‘underside’ of global health was invisible to all but a few critics. I argue that responses to the Covid-19 pandemic have made it visible to all. Perhaps, recognizing what the concept really does, it should be used with caution, or avoided entirely.